Intracranial Rosai–Dorfman disease: a retrospective review of seven consecutive cases - Aly Ibrahim; Tarek H. Elserry; Iman Hewedi; Hamdy Khalil; Husein Moharram; Assem M. Abdel-Latif (Egyptian Journal of Neurosurgery, 2025)
Abstract Background Intracranial Rosai–Dorfman disease (RDD) is a rare entity that usually comes as a surprise diagnosis after surgery. Despite accumulating case reports, the management strategy remains unclear. In this article, we describe our cases series and summarize the pertaining literature with emphasis on different management modalities. Methods We conducted a retrospective review of all patients with intracranial Rosai–Dorfman disease operated at our department over a period of 13 years. Clinical, radiological, and surgical data of these patients were reviewed and summarized. We compared our data to those previously published in the literature about this rare disease. Results All our cases were dural-based extrinsic lesions mimicking meningioma except one cerebellar lesion. Six out of seven cases underwent gross total resection (GTR) and one subtotal resection. Histopathology was confirmed in all cases using immune histochemistry. No patient received adjuvant radio or chemotherapy. There was no local recurrence in any case. One case had distant recurrence. Conclusions Most intracranial RDD presentations are very similar to meningiomas either clinically or radiologically. The definite diagnosis is only confirmed through pathological examination. The rate of recurrence after GTR seems low either in our series or in the literature. There are currently insufficient data to support adjuvant treatment after surgical resection. In case of recurrence, the choice of effective therapeutic strategy is unclear.